Deficit of Local Government Operating Act 2074 B.S. in the Implementation of Federalism and Local Governance in Nepal (Pravaha, 2024)
This study was to examine the relating to deficit of local Government Operating Act (LGOA) 2074 B.S. in the Implementation of Federalism and Local Governance in Nepal. Descriptive and analytical research design was used in this study. The data collected through questionnaire from 200 respondents were used for analysis of Local Government Operating Act 2074 B.S. in the Implementation of Federalism and Local Governance in Nepal are found to be the milestones of federalism in Nepal and the extent of deficits for capacity building efforts have been inadequate and uncoordinated was found high. The findings from this study can provide information about local government operating act. 2074 B.S. It could be helpful to provide some special guidelines to the policy makers for improving local governance. In addition appropriate policy must be adopted and sound communication and information system should be developed.